Big Data’s Exploitation of Social Determinants of Health: Human Rights Implications - Wood, Sarah (Science and Technology Law Review, 2021)
This Article acknowledges the necessity of including social determinants of health (SDH) data in healthcare planning and treatment but highlights the lack of regulation around the collection of SDH data and potential for violating consumers’ basic rights to be treated equally, protected from discrimination, and to have their privacy respected. The Article analyzes different approaches from the U.S. and EU and proffers the global application of the GDPR plus data human rights provisions as the most sustainable option in a world where technology is ever-changing.